Exploring the Impact of Virtual Student Exchange Program on Personal and Speaking Proficiency Development of Indonesian EFL Students - Susandi, Ni Kadek Ary; Rusanti, Putu; Wismadewi, I Gusti Agung Galuh (Universitas Cokroaminoto Palopo, 2023)
Previous studies have shown that studying abroad such as participating in a student exchange program affects the second language (L2) learning outcomes. However, it has yet to be proven whether a short-term experience, such as participation in a virtual student exchange program has a measurable impact on L2 or foreign language development. The present study examines the improvement of English learners speaking skills after participating in a six-week international virtual student exchange program on Asian culture. It is a collaboration among health education institutions in Indonesia, Thailand, Japan, and The Philippines. This study employed quantitative and qualitative methods. Ten Indonesian EFL students were involved in this study and their speaking proficiency was measured before and after participating in the virtual program. A structured interview was also conducted to yield more information on their experience in the program. Statistic findings indicated a significant difference between the students’ speaking proficiency before and after the program (Sig. = 0.004 < 0.05), which meant that their English-speaking proficiency improved over six weeks. The statistical findings are consistent with the student's report stating that they felt more confident and comfortable speaking in English upon participation in the program. These findings extend our understanding that a short-term virtual student exchange experience significantly impacts the speaking proficiency and personal development of Indonesian EFL students. The results of this study imply that efforts to support such international virtual programs should continue.